Bolivar the liberator of Latin America - Harvey, Robert (Skyhorse, 2011)
Profiles the South American general and revolutionary who helped liberate several South American countries from Spanish domination
Includes bibliographical references and index
Keywords: Bolívar, Simón / 1783-1830; Bolívar, Simón -- 1783-1830; Heads of state / South America / Biography; Geschichte; Latin America / History / Wars of Independence, 1806-1830; South America / History / Wars of Independence, 1806-1830; South America / History; Lateinamerika; Biografie